2009
DOI: 10.1158/0008-5472.can-08-2807
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Smoke Induces Polycomb-Mediated Repression of Dickkopf-1 in Lung Cancer Cells

Abstract: Limited information is available about epigenetic mechanisms by which cigarette smoke enhances the initiation and progression of lung cancer. To examine this issue, A549 and Calu-6 lung cancer cells were cultured in normal media with or without tobacco smoke condensate (TSC) under clinically relevant exposure conditions. Ten-day TSC exposure dramatically increased the tumorigenicity of lung cancer cells in nude mice. Microarray and quantitative reverse transcription-PCR (RT-PCR) experiments revealed that this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
135
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(141 citation statements)
references
References 50 publications
5
135
0
1
Order By: Relevance
“…10 The effects of CS on normal nontransformed airway cells appear to differ from those that are malignantly-transformed. For example, Hussain et al showed that CS directly engaged polycomb machinery to activate canonical Wnt signaling in the maintenance of cancer stem cells, 37 while Marsit et al reported CS-induced Wnt signaling through epigenetic silencing of the extracellular Wnt antagonist, soluble frizzled receptor protein (SFRP). 38 The complexity of mechanisms regulating canonical Wnt signaling in response to CS might reflect a stage-specific control of Wnt signaling activation during the multistep process of malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…10 The effects of CS on normal nontransformed airway cells appear to differ from those that are malignantly-transformed. For example, Hussain et al showed that CS directly engaged polycomb machinery to activate canonical Wnt signaling in the maintenance of cancer stem cells, 37 while Marsit et al reported CS-induced Wnt signaling through epigenetic silencing of the extracellular Wnt antagonist, soluble frizzled receptor protein (SFRP). 38 The complexity of mechanisms regulating canonical Wnt signaling in response to CS might reflect a stage-specific control of Wnt signaling activation during the multistep process of malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…PcG complexes comprise the machinery of transcriptional regulatory processing in homeotic (HOX) gene expression (12,30), and several cellular responses, including cell cycle (31), senescence (20), cancer (11,(32)(33)(34), cell fate decisions (33) and stem cell differentiation or maintenance (11,35). PcG consists of two distinct protein complexes, PRC1 and PRC2, which are best characterized in the repression of transcription.…”
Section: Volume 287 • Number 38 • September 14 2012mentioning
confidence: 99%
“…PRC2 maintains and establishes tumor suppressor gene silencing during carcinogenesis (36 -37). Increases in SUZ12, a key component of PRC2, coincide with transformation and many cancers (14,34,36,38). PRC1 recognizes the histone H3K27 methylation and recruits PRC2 to PcG target genes resulting in transcriptional repression (15).…”
Section: Volume 287 • Number 38 • September 14 2012mentioning
confidence: 99%
“…Recently, Hussain et al reported that tobacco smoke engaged polycomb repressor complexes that contained EZH2 to mediate epigenetic silencing of Dickkopf-1 (a Wnt signaling antagonist) and enhanced the malignant phenotype of lung cancer cells. 37 Although the mechanism by which EZH2 mediates tumor aggressiveness is unclear, recent studies indicate that EZH2 mediates transcriptional silencing of a tumor suppressor gene E-cadherin (by trimethylation of H3 lysine 27). 38,39 Yu et al demonstrated that EZH2 may mediate increased invasiveness and metastasis by silencing several downstream targets in addition to E-cadherin, including the adrenergic receptor (ADR) ADRB2.…”
Section: Bmi1 and Ezh2 Expression In Nsclc/kikuchi Et Almentioning
confidence: 99%